Analysis of Factors Affecting Public Interest in Investing in the Capital Market (Case Study on the Paluta Community) - Epa Purnama Sari Harahap; Purnama Rahmadani Silalahi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this study is to find out how the Paluta community's opinion on the factors that influence people's interest in investing in the capital market, of the 28 respondents who filled out the questionnaire, the Paluta community knew what investment in the capital market was. And investment in the capital market is an investment activity in the form of buying company shares (securities). So by buying company shares, you become the owner of the company. In addition to stocks, investment products in the capital market are mutual funds and bonds.